1981
DOI: 10.1177/000331978103201106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Intrinsic Sympathomimetic Activity of Beta Blockers Used in Angina

Abstract: beta-Blockers are effective in the symptomatic relief of angina pectoris by decreasing myocardial oxygen demand during effort and emotional stress. Agents with ISA such as pindolol produce effective beta-blockade during effort or emotional stress while conferring significant protection from myocardial depression and bradycardia at rest. In addition, agents with ISA have been shown to depress respiratory function to a lesser extent and to induce fewer peripheral vascular side effects than compounds devoid of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Other comparative studies by Frishmann (78) and Thadani (79) showed no difference between propranolol and pindolol. Dwyer et al (80) compared 15 and 30 mg pindolol daily with placebo in 12 anginal subjects and concluded that whilst it reduced trinitrin consumption and the number of anginal episodes, it did not increase exercise tolerance.…”
Section: Efficacymentioning
confidence: 84%
“…Other comparative studies by Frishmann (78) and Thadani (79) showed no difference between propranolol and pindolol. Dwyer et al (80) compared 15 and 30 mg pindolol daily with placebo in 12 anginal subjects and concluded that whilst it reduced trinitrin consumption and the number of anginal episodes, it did not increase exercise tolerance.…”
Section: Efficacymentioning
confidence: 84%
“…A primary therapeutic indication of celiprolol will be in the treatment of angina pectoris in patients with coronary heart disease. The efficacy of P-adrenoceptor antagonists in angina has been well established (25,43,46,52) and probably is based on @,-antagonism only (61). As a cardioselective @-antagonist, celiprolol should be especially effective for this indication.…”
Section: Antianginal Effectsmentioning
confidence: 99%